Pemerolehan Kata Pemelajar BIPA UM Ditinjau dari Segi Sintagmatik dan Paradigmatik - Yohanna Nirmalasari; A. Syukur Ghazali; Gatut Susanto (Pascasarjana Universitas Negeri Malang, 2018)
This study attempts to described acquisition Indonesian word wrote language in terms of terms syntagmatic and paradigmatic. This research used the study text. The results showed that (1) the acquisition of the word in terms of syntagmatic appears on the placement of the words in the phrase that pays attention to the type of function words written by learners respectively. The function of S and O always occupied noun and a good basic words or words that form noun form. The function P is always occupied by the verbs or basic word and word formats that use the prefixes used to form verbs, adjectives, and nouns in the ekuatif sentence. The function Pel is always occupied by the noun or noun form of repetition that forms, as well as the compound form of the noun form. The function Ket is always occupied by noun or creations of the basic form of the noun + adjectives, nouns + pronouns or nouns only. (2) The word acquisition in terms of terms paradigmatic shows that alignment meaning depending on the type of and type of a word used by the learners, from said concrete into a abstract and the relationship between the interpretation, namely synonym relations, hyponymy, and word grammatical. Penelitian ini bertujuan untuk mendeskripsikan pemerolehan kata bahasa Indonesia tulis ditinjau dari segi sintagmatik dan paradigmatik. Penelitian ini menggunakan pendekatan kajian teks. Hasil penelitian menunjukkan bahwa (1) pemerolehan kata ditinjau dari segi sintagmatik tampak pada penempatan kata secara fungsi kalimat yang memperhatikan jenis kata yang ditulis oleh pemelajar secara berturut-turut. Fungsi S dan O selalu ditempati nomina dan pronomina baik kata dasar maupun kata bentukan yang membentuk nomina. Fungsi P selalu diduduki oleh verba atau kata dasar dan kata bentukan yang menggunakan prefiks yang berfungsi untuk membentuk kata kerja, adjektiva, dan nomina pada kalimat ekuatif. Fungsi Pel selalu diduduki oleh nomina atau bentuk pengulangan yang membentuk nomina, serta bentuk pemajemukan yang membentuk nomina. Fungsi Ket diduduki oleh nomina atau bentukan dari bentuk dasar dari nomina + adjektiva, nomina + pronomina, atau nomina saja. (2) Pemerolehan kata ditinjau dari segi paradigmatik menunjukkan bahwa kesejajaran makna bergantung pada jenis dan bentukan kata yang digunakan oleh pemelajar, yakni dari kata konkret ke kata abstrak dan hubungan antar maknanya, yakni hubungan sinonimi, hiponimi, dan gramatika kata.